Body language for dummies - Kuhnke, Elizabeth (Chichester, West Sussex, UK John Wiley & Sons, Ltd., 2015)
This is your ideal guide to understanding other people, and helping them understand you. Body language is a critical component of good communication, and often conveys a bigger message than the words you say. This book teaches you how to interpret what people really mean by observing their posture, gestures, eye movements, and more, and holds up a mirror to give you a clear idea of how you're being interpreted yourself. This updated third edition includes new coverage of virtual meetings, multicultural outsourcing environments, devices, and boardroom behaviours for women, as well as insight into Harvard professor Amy Cuddy's research into how body language affects testosterone and cortisol, as published in the Harvard Business Review. Body language is a fascinating topic that reveals how the human mind works. Image and presentation are crucial to successful communication, both in business and in your personal life. This book is your guide to decoding body language, and adjusting your own habits to improve your interactions with others. * Become a better communicator without saying a word * Make a better first (and second, and third...) impression * Learn what other people's signals really mean * Transform your personal and professional relationships Realising what kind of impression you give is a valuable thing, and learning how to make a more positive impact is an incredibly useful skill. Whether you want to improve your prospects in job seeking, dating, or climbing the corporate ladder, this book helps you translate the unspoken and get your message across.
Getting started with body language -- Starting at the top -- The trunk: limbs and roots -- Putting the body into social and business context -- The part of tens.
Includes index.
Keywords: Body language